Educação especial: um olhar para o profissional de apoio no município de Abaetetuba-PA - SENA JÚNIOR, Benedito Nogueira (2022)
The research addresses concepts in the field of special education and its implications. It aims to Analyse the public policies related to professionals working in this area and highlighting some regulations that contributed to guarantee the right of students of special education in the regular school network, having as object of study an experience of a school support professional, reflecting on the main barriers and obstacles that he encounters to carry out the quality teaching-learning process for people with disabilities. this study is of a qualitative nature where scientific articles from the sciELO databases and the Digital Library of Monographs were used as references, document analysis and a structured interview with ten questions were carried out.